A novel Class of Lomax Parameters Estimation Using Bayesian and Non-Bayesian Approach - Salma Omar Bleed; Aaida Omran Omar saddi (African Journal of Advanced Pure and Applied Sciences, 2025)
A new class of Lomax distribution has been introduced using DUS method, called the L-Lomax distribution. Mathematical formulations with some properties of L-Lomax distribution are provided. Maximum likelihood estimators and Bayesian estimators, corresponding to two informative priors gamma and exponential based on complete and incomplete data, are obtained. Monte Carlo simulations for different L-Lomax generated random samples ranging from 500 to 50000 were performed. Additionally, various informative priors such as exponential, Weibull, gamma, beta and chi-square are used to illustrate the flexibility of the proposed distribution among other competitive models.